Deriving literature-based benchmarks for surgical complications in high-income countries: a protocol for a systematic review and meta-analysis. Issue 5 (9th May 2017) - Brindle, Mary E; Roberts, Derek J; Daodu, Oluwatomilayo; Haynes, Alex Bernard; Cauley, Christy; Dixon, Elijah; La Flamme, Claude; Bain, Paul; Berry, William
Abstract : Introduction: To improve surgical safety, health systems must identify preventable adverse outcomes and measure changes in these outcomes in response to quality improvement initiatives. This requires understanding of the scope and limitations of available population-level data. To derive literature-based summary estimates of benchmarks of care, we will systematically review and meta-analyse rates of postoperative complications associated with several common and/or high-risk operations performed in five high-income countries (HICs). Methods and analysis: An electronic search of PubMed, Embase, Web of Science, Cochrane Central, the NHS Economic Evaluations Database and Health Technology Assessment database will be performed to identify studies reviewing national surgical complication rates between 2000 and 2016. Two reviewers will screen titles and abstracts and full texts of potentially relevant studies to determine eligibility for inclusion in the systematic review. We will include English-language publications using data from health databases in the USA, Canada, the UK, Australia and New Zealand. We will include studies of patients who underwent hip or knee arthoplasty, appendectomy, cholecystectomy, oesophagectomy, abdominal aortic aneurysm repair, aortic valve replacement or coronary artery bypass graft. Outcomes will include mortality, length of hospital stay, pulmonary embolism, pneumonia, sepsis or septic shock, reoperation, surgical site infection, wound dehiscence/disruption, blood transfusion, bile duct injury, stroke and myocardial infarction. We will calculate summary estimates of cumulative incidence, incidence rate, prevalence and occurrence rate of complications using DerSimonian and Laird random effects models. Heterogeneity in these estimates will be examined using subgroup analyses and meta-regression. We will correlate findings within contemporary clinical databases. Ethics and dissemination: This study of secondary data does not require ethics approval. It will be presented internationally and published in the peer-reviewed literature. Results will inform a future quality improvement tool and provide benchmarks of surgical complication rates within HICs. Trial registration: International Prospective Register of Systematic Reviews (PROSPERO). Registration number CRD42016037519.